Physiological and psychological response modelling of the helicopter pilot through vibration simulation - Khaksar, Z.; Anavatti, S.; Shankar, K.; Ceruti, A. (My University, 2017)
This research focuses on the integrated simulation of helicopter-pilot system to predict pilot’s physiological and psychological responses to the vibration. This paper describes the approach of integration of helicopter structural model to the aerodynamic forcing function and to the pilot-seat model. The physiological and psychological responses at 5 Hz are calculated based on vibration transmission ratio of the pilot’s body segments. The pilot’s Physiological responses including heart rate, highest blood pressure, lowest blood pressure, respiration rate and saliva secretion quantity are presented. Tired eyes, irritation, dizziness, yawning, sleepiness and headache as psychological reactions are provided. The integrated simulation approach of helicopter-pilot system can be used for pilot health and comfort assessments, helicopter structural and cockpit and seat design.